Blackbird fly - Kelly, Erin Entrada 1977- (Greenwillow Books, an imprint of HarperCollins Publishers, 2015)
Bullied at school, eighth-grader Apple, a Filipino American who loves the music of the Beatles, decides to change her life by learning how to play the guitar